Chemopreventive effect of modified zeng-sheng-ping on oral squamous cell carcinoma by regulating tumor associated macrophages through targeting tnf alpha induced protein 6 - Jiaqi Wang; Feiran Lin; Yongxiang Zhou; Yuyi Cong; Sen Yang; Sujuan Wang; Xiaobing Guan (BMC, 2024)
Abstract Background Oral squamous cell carcinoma (OSCC) is the most common malignancy of the head and neck. Zeng-Sheng-Ping, composed of Sophora tonkinensis Gagnep., Bistorta officinalis Delarbre, Sonchus arvensis L., Prunella vulgaris L., Dioscorea bulbifera L., and Dictamnus dasycarpus Turcz., was regarded as an anti-cancer drug with significant clinical efficacy, but was discontinued due to liver toxicity. Our research group developed a modified Zeng-Sheng-Ping (ZSP-M) based on original Zeng-Sheng-Ping that exhibited high efficiency and low toxicity in preliminary investigations, although its pharmacodynamic mechanism is still unclear. Here, we aimed to elucidate the pharmacodynamic material basis of ZSP-M and investigate its chemopreventive effect on OSCC by modulating tumor associated macrophages (TAMs). Methods Components of ZSP-M were characterized using ultra-performance liquid chromatography-mass spectrometry. Chemopreventive effect induced by ZSP-M against experimental oral cancer was investigated using the 4-nitroquinoline N-oxide precancerous lesion mouse model. RNA sequencing analysis was used to gain a global transcriptional view of the effect of ZSP-M treatment. A cell co-culture model was used to study the targeted effect of ZSP-M on TAMs and the biological properties of OSCC cells and to detect changes in TAM phenotypes. The binding of ZSP-M active compounds to TNF alpha induced protein 6 (TNFAIP6) protein was analyzed by molecular docking and dynamic simulation. Results Forty main components of ZSP-M were identified, the most abundant of which were flavonoids. ZSP-M inhibited the degree of epithelial dysplasia in precancerous lesions by inhibiting the expression of the TNFAIP6 and CD163 proteins in the precancerous lesions of the tongue. ZSP-M inhibited proliferation, colony formation, migration and invasion of SCC7 cells by targeting TAMs. ZSP-M reduced the expression of CD163+ cells, inhibited the expression of TNFAIP6 protein, Arg1 mRNA and Il10 mRNA in TAMs, and reduced IL-10 cytokine release in the co-culture environment. This effect was maintained after the addition of recombinant TNFAIP6 protein. Computer simulations showed that trifolirhizin and maackiain are well-connected to TNFAIP6. Conclusions ZSP-M counteracts the immunosuppressive action of TAMs by specific targeting of TNFAIP6, thereby exerting chemopreventive activity of OSCC.